Internationally targeted digital marketing in business-to-business context : Case of a Finnish event venue company - Päivölä, Viivi-Anna (My University, 2018)
Digital marketing is a buzzword that is on everyone’s lips. Everyone should know what it is, every company should do it and know how to do it right. However, the huge number of digital marketing channels has gotten many companies confused. The channels are not being used effectively and the knowledge on all the potential of online marketing is minimal. This is especially the case with companies operating in B2B marketing, in amongst whom notably social media has been neglected as a marketing tool of affordable reach and brand building. The research is done from the point of view of event management and B2B service marketing, and the research method was qualitative. The research was conducted with utilizing a semi-structured interview and secondary-data analysis, and it was done as an assignment to a Finnish company, operating in the field of event management and venue services. The aim of the research was to find best practices utilized in B2B digital marketing, that the assignment company could utilize to enhance their own digital marketing operations. Overall 12 Nordic companies were researched to offer a comprehensive understanding of the prevalence practices in the field of event management regarding digital marketing. In the study was revealed, that many companies still lack a cohesive online strategy and that the value of utilizing different channels has not been understood. Social medias are acquired just for the sake of having them, but they are not updated regularly and the content is not necessary relevant to its’ context. The decision makers in B2B are becoming younger and are the ones that have not lived without the Internet, hence the proficient utilization if it is becoming crucial to B2B marketers as well.